(untitled) (Journal of the College of Education for Women, 2019)
The aim of the study is to diagnose the real level of technology usage in teaching and learning EFL at university from teachers and students’ viewpoints, and see if it is possible to achieve something of the researchers’ dream - accessing top universities. Two questionnaires have been used to measure the range of technology usage in Colleges of Education for Women, Baghdad and Iraqi Universities, and College of Basic Education. The results have shown that the reality of using technology is still away from the dream. The results have been ascribed to two reasons: The first is the little knowledge of using technology in teaching, and the second is that technology is not included in the curriculum.